Can a Short Term of Repeated Ejaculations Affect Seminal Parameters? (2016)
ABSTRACT: The aim of the study was to assess the effect of four repeated ejaculations on the same day at two-hour intervals on conventional and functional semen parameters. Methods: Three healthy men (32±3.6 years) donated the first semen samples after 3–4 days of sexual abstinence followed by three subsequent samples on the same day at two-hour interval each. Semen samples were processed and analyzed according to the World Health Organization (WHO) 2010 guidelines. Furthermore, intracellular reactive oxygen (ROS) production, sperm DNA fragmentation and mitochondrial function were evaluated by flow cytometry. Results: An overall decreasing trend was noted in the conventional semen parameters at second, third and fourth evaluations after two hours of abstinence in comparison to first evaluation after 3–4 days of abstinence. The statistical comparison of the conventional semen parameters at fourth evaluation after 2 hr of abstinence revealed significant reduction (p<0.05) in the parameters of concentration, total sperm count and total motile sperm count at fourth evaluation. The functional parameter of intracellular ROS production showed a decreasing trend with each subsequent evaluation, the difference being significant (p<0.05) at fourth evaluation in comparison to first evaluation. An increasing trend was noted for DNA fragmentation index (DFI), although it remained within acceptable levels (<29%). The ΔΨm high permatozoa and the integrity of the plasma membrane remained stable throughout the evaluations. Conclusion: The findings of the present study indicate the potential use of additional semen samples with repeated ejaculations at short abstinence times in assisted reproduction procedures particularly from severe oligospermic men.